Relativistic nonlinear Thomson scattering of excited electron in ultra-tightly focused circularly polarized laser pulses with different beam waist radius - Zheng, Qianmin; Li, Jiachen; Wang, Zi; Tian, Youwei (Frontiers in Physics, 2025)
Based on Thomson scattering classical theory and single-electron model, we explore the influence of variations in the laser beam waist radius on the interaction between an ultra-tightly focused (UTF) laser and off-axis electron. In practical experiments, off-axis collisions predominate, and our study specifically addresses this scenario. Under UTF conditions (b0=2 λ0), electron experience significant asymmetric forces, leading to deviations in axial trajectories, acceleration, and oscillations in energy. Simultaneously, observable asymmetries emerge in the electron’s radiated power and spectrum, gradually diminishing as the beam waist radius increases. These findings are pivotal for generating ultrashort pulses, particularly in ultrashort optics, and hold significance for applications leveraging nonlinear inverse Thomson scattering radiation.